Exercise enhances skeletal muscle regeneration by promoting senescence in fibro-adipogenic progenitors - Saito, Yuki (Nat Commun, 2020)
Idiopathic inflammatory myopathies cause progressive muscle weakness and degeneration. Since high-dose glucocorticoids might not lead to full recovery of muscle function, physical exercise is also an important intervention, but some exercises exacerbate chronic inflammation and muscle fibrosis. It is unknown how physical exercise can have both beneficial and detrimental effects in chronic myopathy. Here we show that senescence of fibro-adipogenic progenitors (FAPs) in response to exercise-induced muscle damage is needed to establish a state of regenerative inflammation that induces muscle regeneration. In chronic inflammatory myopathy model mice, exercise does not promote FAP senescence or resistance against tumor necrosis factor–mediated apoptosis. Pro-senescent intervention combining exercise and pharmacological AMPK activation reverses FAP apoptosis resistance and improves muscle function and regeneration. Our results demonstrate that the absence of FAP senescence after exercise leads to muscle degeneration with FAP accumulation. FAP-targeted pro-senescent interventions with exercise and pharmacological AMPK activation may constitute a therapeutic strategy for chronic inflammatory myopathy.